Record of anthropogenic impact on the Western Irish Sea mud belt. (March 2015) - Coughlan, M.; Wheeler, A.J.; Dorschel, B.; Lordan, C.; Boer, W.; Gaever, P.van; Haas, H.de; Mörz, T.
Highlights: We investigate 5 cores from the Irish Sea using a multi-proxy approach. We assess multibeam echosounder and backscatter data from the same area. We analyse these cores for anthropogenic radionuclides using gamma spectrometry. Downcore radionuclide activity was related to known output levels from Sellafield. The impact of trawling was found to result in significant amounts of sediment loss. Abstract: Six cores, geophysical data (multibeam bathymetry), surface grab samples and video photography were collected from the area of the Western Irish Sea Mud Belt (WISMB). These data were analysed to determine the radionuclide input from the Sellafield nuclear facility on the eastern (UK) seaboard of the Irish Sea, and subsequently to assess the influence of bottom trawling and bioturbation on the surface and near-surface sediments. Results show significant changes in the sedimentation and geochemical regime in the WISMB due to anthropogenic causes (bottom trawling and radionuclides derived from the power plant). These changes are consistent with the concept of the Anthropocene time period. Levels of anthropogenic radionuclides measured in two of the cores enabled construction of a chronology correlated with recorded values of discharge from the Sellafield facility. Excess 210 Pb and the anthropogenic radionuclide 137 Cs proved useful as stratigraphic marker tools. These radionuclide data also enabled quantification of the effects of trawling, which was visible on acoustic seabed maps. Bottom trawling has removed an estimated 20–50 cm of the upper seabed.